2009
DOI: 10.1021/bi801820q
|View full text |Cite
|
Sign up to set email alerts
|

Convulxin Forms a Dimer in Solution and Can Bind Eight Copies of Glycoprotein VI: Implications for Platelet Activation

Abstract: Convulxin (CVX) is a C-type lectin-like protein from the venom of the South American rattlesnake that functions as a potent agonist of the platelet collagen receptor glycoprotein VI (GPVI). Although CVX is widely used as a platelet agonist, the molecular basis for its extremely high potency is not clear. In order to delineate possible mechanisms for CVX-induced GPVI activation, we used analytical ultracentrifugation to determine the assembly state of CVX in solution and surface plasmon resonance in order to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…It is a heterodimeric tetramer protein of approximately 84,000 Da size, with one subunit of 135 amino acid residues and a second of 125 amino acid residues (Leduc and Bon, 1998), and belongs to the family of the snaclecs (snake C-type lectins; Polgar et al, 1997;Clemetson et al, 2009). Within mammalian prey, convulxin acts by inducing platelet aggregation through binding and clustering of the p62/GPVI collagen receptor (Jandrot-Peruus et al, 1997) and can bind eight GPVI (Horii et al, 2009) (Fig. 5).…”
Section: Convulxin: a Unique And Powerful Collagen Receptor Agonistmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a heterodimeric tetramer protein of approximately 84,000 Da size, with one subunit of 135 amino acid residues and a second of 125 amino acid residues (Leduc and Bon, 1998), and belongs to the family of the snaclecs (snake C-type lectins; Polgar et al, 1997;Clemetson et al, 2009). Within mammalian prey, convulxin acts by inducing platelet aggregation through binding and clustering of the p62/GPVI collagen receptor (Jandrot-Peruus et al, 1997) and can bind eight GPVI (Horii et al, 2009) (Fig. 5).…”
Section: Convulxin: a Unique And Powerful Collagen Receptor Agonistmentioning
confidence: 99%
“…Tetramers are formed by covalent disulfide linkages(Murakami et al, 2003) Horii et al (2009). determined that convulxin exists as the dimer of a4b4 tetramers in solution, resulting in eight potential binding sites for GPVI.…”
mentioning
confidence: 99%
“…14,15 It also was suggested that CVX exists in solution as a dimer of α4β4 rings and contains 8 distinct GPVI-binding sites and binds GPVI with high-binding affinities. 16 Also, presence of 2 distinct GPVI-binding surfaces on the (α4β4)2 CVX dimers allows CVX to both cluster GPVI on a single cell and to cross-link target cells via GPVI.…”
Section: See Accompanying Editorial On Page 1266mentioning
confidence: 99%
“…134 Convulxin, a C-type lectin-like protein from the venom of the South American rattlesnake that functions as a potent agonist of GPVI, has been reported recently to form a dimer in solution and bind eight copies of GPVI. 248 Other MIRRs. Human TREM-1 receptor has been shown to exist as a "head-to-tail" dimer in crystal, suggesting that the dimeric TREM-1 most likely contains two distinct ligand-binding sites.…”
Section: Supportive Evidence For the School Model Of Multichain Recepmentioning
confidence: 99%